The role of endoscopic resection for selected patients with sinonasal squamous cell carcinoma. Issue 1 (February 2021) - Nakamaru, Yuji; Suzuki, Masanobu; Kano, Satoshi; Mizumachi, Takatsugu; Tsushima, Nayuta; Suzuki, Takayoshi; Honma, Aya; Nakazono, Akira; Kimura, Shogo; Onimaru, Rikiya; Yasuda, Koichi; Shirato, Hiroki; et al.
Abstract: Objective: Despite of rapid advances in endoscopic surgery, the gold standard for sinonasal squamous cell carcinoma (SNSCC) surgery has remained the open approach with en-block resection due to the aggressive nature of SNSCC, including frequent recurrence and high mortality rate. For that reason, few studies have focused on SNSCC treated by endoscopic surgery alone. The objective of this study was to evaluate the usefulness of endoscopic surgery for patients with SNSCC. Methods: A retrospective analysis was performed for 15 consecutive SNSCC patients who underwent endoscopic surgery without an open approach. We carefully selected patients whose tumor attachment sites could be fully visualized and completely resected through an endonasal approach. Results: Of the fifteen patients, 4 patients (27%) were diagnosed with T1, 7 (47%) with T2, 4 (27%) with T3, and no patients with T4a or T4b disease. Four of the 15 (27%) patients showed positive surgical margins. The 5-yr overall survival, disease-specific survival, and local control rate was 72.4%, 79.6%, and 92.9%, respectively. The 5-yr disease-specific survival for T1, T2, and T3 disease was 100% and 75% and 75%, respectively. Patients with negative surgical margins had a better disease-specific survival rate than did those with positive surgical margins ( p  = 0.0253). Conclusion: Endoscopic surgery for patients with SNSCC appears to afford an effective method in selected cases. The achievement of negative surgical margins with a good view of the tumor attachment site was considered to be critical to the management of SNSCC.